Interactions Among Ovarian Hormones and Time of Testing on Behavioral Sensitization and Cocaine Self-Administration - Yang, Hongyan (2007)
Ovarian hormones play a role in the use of drugs of abuse in women. In female rats estradiol has been shown to enhance acquisition of cocaine self-administration and behavioral sensitization induced by repeated cocaine treatment. Experiments were conducted to determine the effects of estradiol and/or progesterone on cocaine self-administration and behavioral sensitization to cocaine (10 mg/kg; in animals with unilateral 6-hydroxydopamine lesions). Five groups of ovariectomized females were tested: 1) oil vehicle; 2) estradiol (E); 3) progesterone (P); 4) estradiol and progesterone given concurrently (EPC); and 5) estradiol and progesterone given sequentially (EPS 3 days of estradiol, 1 day progesterone, 1 day oil). All animals were tested during the dark phase of the light:dark cycle at ZT1600 and ZT2000-2100. BEHAVIORAL SENSITIZATION RESULTS: There was substantial conditioned turning throughout the habituation periods, and all animals exhibited behavioral sensitization with repeated cocaine treatment. Multivariate analysis indicated a significant effect of hormone treatment, time of day and day of testing. When individual groups were compared, however, only at ZT1600 did the E-treated and the EPS-treated animals show a trend (p<0.06) for greater behavioral sensitization to cocaine relative to the oil-treated animals. SELF-ADMINISTRATION RESULTS: All groups showed rapid acquisition of cocaine self-administration at 0.3 mg/kg/inf, so we did not see an effect of ovarian hormones on acquisition, or a difference between groups tested at ZT1600 vs. ZT2100 (p<0.005). There was, however, enhanced total intake of cocaine at 0.75 mg/kg/inf in the E and the EPS groups. Concurrent administration of progesterone with estradiol counteracted the effect of estradiol on cocaine intake at 0.75 mg/kg/inf, while progesterone alone did not enhance cocaine self-administration.